English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-10-04 18:54:42 · 10 answers · asked by Revan M 1 in Science & Mathematics Mathematics

10 answers

lets continue the statement:
for 6(x-1)-2(x-1)
con. 6x-6-2x-2
con. 4x-4
it's mean there is no answer about your question, because you dont specify the equation (not complete equation), or you dont specify what variable that you ask.
may be the complete question like this:
6(x-1)-2(x-1)=0; what is x?
tx.

2006-10-04 19:10:16 · answer #1 · answered by eL'do-radO 3 · 0 0

6(x-1)-2(x-1)=4(x-1)

2006-10-08 11:38:47 · answer #2 · answered by yupchagee 7 · 0 0

6(x-1) - 2(x-1)
6x - 6 - 2x + 2 > Distribute to the parentheses
6x - 2x - 6 + 2 > Add the like terms
4x - 4 > Your solution

or you can also simplify since the parentheses are like

(6 - 2)(x - 1)
(4)(x -1)
4x - 4

2006-10-04 19:09:46 · answer #3 · answered by Anonymous · 0 0

6(x - 1) - 2(x - 1) = 0

6x - 6 - 2x + 2 = 0

The distributive property

4x - 4 = 0

Collecting like terms

4x = 4

4x/4 = 4/4

Dividing both sides of the equation by 4

x = 1

The answer is x = 1

The solution set is { 1 }

Insert the x value into the equation

- - - - - - - - - - - - - - - - - - - - - - - - - -

6(x - 1)- 2(x - 1)= 0

6(1 - 1) - 2(1 - 1) = 0

6(0) - 2(0) = 0

0 - 0 = 0

0 = 0

2006-10-05 00:32:15 · answer #4 · answered by SAMUEL D 7 · 0 0

(x-1)(6-2)=4(x-1)

2006-10-04 18:56:22 · answer #5 · answered by raj 7 · 0 0

6x - a million .. 2x —-— – — = 3 .. 5 ... ... 3 Multiply both area through 15 (LCM of three and 5) 3(6x -a million) - 5(2x) = 15*3 subsequently 18x - 3 - 10x = 40 5 ........................ ******* So 8x = 40 8 subsequently x = 6 examine!! (6*6 -a million)/5 - 2*6/3 = 35/5 - 12/3 = 7 - 4 = 3 YESSSSSSSSS!! it quite is more suitable than x = 2 can do!!!!! (as "jenh42002" and "addicted" are suggesting because the answer through their very incorrect go multiplying technique as this isn't a setup for difficulty-free go multiplying without FIRST simplifying the fractions on the left hand fringe of the equation ie 6x - a million .. 2x —-— – — = . 5 ... ... 3 3(6x - a million) - 5*2x —————— = ........ 15 18x - 3 - 10x —————— = ........ 15 8x - 3 ——— .. 15 NOW go multiply!!! ie 8x - 3 ——— = 3 .. 15 So 8x - 3 = 40 5 so 8x = 40 8 so x = 6 Alternately 6x - a million .. 2x —-— – — = 3 . 5 ... ... 3 So 6x - a million ......... 2x —-— = 3 + — . 5 ............... 3 So 6x - a million .. 2x + 9 —-— = —-— . 5 .......... 3 And now go multiply for your heart's content fabric 3(6x - a million) = 5(2x + 9) 18x - 3 = 10x + 40 5 and so on..... (See line ******* above as that is only a mild version of that line)

2016-12-04 07:07:40 · answer #6 · answered by Anonymous · 0 0

(x-1)(6-2) = 4(x-1) = 4x - 4.

2006-10-04 20:12:54 · answer #7 · answered by Anonymous · 0 0

Take common denominator to one side...everything else to the other..
(6-2)(x-1)

4 (x-1)

4x-4

answer = 4x-4

2006-10-04 19:02:40 · answer #8 · answered by Player 3 · 0 0

simple 4x-4

2006-10-04 19:17:10 · answer #9 · answered by Nick 3 · 0 0

6(x-1)-2(x-1)

6x-6-2x+2

6x-2x-6+2

4x-4

4(x-1)

2006-10-05 11:53:47 · answer #10 · answered by Melanie G 1 · 0 0

fedest.com, questions and answers